A comparison of pile performance base on static formulas and dynamic load test - Ramli, Muhd. Harris (2006)
Since the early of pile static formula suggested by Meyerhof (1956) up until now, several pile design method is being proposed. Between one method and another, result differences are still questionable. This study is conducted base on driven pile 300 mm diameter spun pile constructed in Malaysia on sand or fine soil. This is to determine the differences between several pile design methods by Meyerhof (1976), Janbu (1976), Vesic (1977), Coyle and Castello (1981), ?? method (1985) and ?? method (1972) with the End-bearing capacity and Skin Resistance capacity value from dynamic load test using Pile Driving Analyzer (PDA). All the design method is also analyzed by using soil friction angle correlation by Schmertmann (1975), Peck, Hanson and Thornburn (1974) and Hatanaka and Uchida (1996). From analysis it can be found that Meyerhof, Coyle and Castello, and ?? method are the most conservative which its value lower or almost near the PDA value. Then follow by Janbu method and ?? method which its value almost near PDA or slightly above it. Vesic method is found to be very unconservative which it value well above PDA value. From this study it can be conclude that it is recommended to use either Meyerhof or Janbu Method for estimating end-bearing capacity in sand and silt. For skin resistance in sand it recommended using Meyerhof method. Finally for estimating skin resistance in clayed soil it is recommended to use ?? method.